Sputtering target material and its manufacturing method

JP7641786B2Active Publication Date: 2025-03-07SANYO SPECIAL STEEL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021052609
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-26
Publication Date
2025-03-07
Estimated Expiration
2041-03-26

AI Technical Summary

Benefits of technology

【0014】 本発明に係るスパッタリングターゲット材は、その材質が希土類元素を含む合金であるにも関わらず、耐割れ性に優れている。このターゲット材では、その製造中及びスパッタリング時の破損が回避される。このターゲット材の生産効率は、高い。しかも、このターゲット材を用いたスパッタリングにより得られるトンネル磁気抵抗膜は、磁気性能に優れている。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641786000003
    Figure 0007641786000003
  • Figure 0007641786000004
    Figure 0007641786000004
  • Figure 0007641786000001
    Figure 0007641786000001
Patent Text Reader

Abstract

To provide a sputtering target material with superior cracking resistance and a method of manufacturing the same.SOLUTION: A sputtering target material includes B, a rare earth element RE and an element M, and the rest thereof is an alloy consisting of Co and / or Fe and impurities. The content x of B is 15 to 30 at.%. The rare earth element RE is selected from the group of Pr, Nd, Sm, Gd, Tb, Dy, and Ho. The total content y of the rare earth element RE is 0.1 to 11 at.%. The element M is selected from the group of Cu, Ge, Sn, and Ru. The total content z of the element M is 0.25 to 13.0 at.%. The ratio z / y of the total content z and total content y is 0.5 to 2.5. The sputtering target material is a sintered body of raw material powder including the alloy having this composition.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sputtering target material, and more particularly to a sputtering target material containing a rare earth element and a method for producing the same. [Background technology]

[0002] Tunnel magnetoresistance films are used in magnetic devices such as magnetic heads and magnetic random access memories (MRAMs), etc. Tunnel magnetoresistance films exhibit characteristics such as a high tunnel magnetoresistance (TMR) signal and low switching current density (Jc).

[0003] The tunnel magnetoresistance film has a structure in which, for example, two magnetic layers made of a Co-Fe-B alloy sandwich a shielding layer made of MgO. Magnetic bodies containing boron (B) are known as materials for forming the magnetic layers. Specifically, magnetic bodies having compositions such as Co-B, Fe-B, Co-Fe-B, or those to which Al, Cu, Mn, Ni, etc. are added are exemplified.

[0004] The magnetic layer constituting the tunnel magnetoresistive film is usually obtained by sputtering using a target material made of a Co-Fe-B alloy. JP 2004-346423 A (Patent Document 1) discloses a Co-Fe-B alloy target material in which a boride phase is finely dispersed in a cross-sectional microstructure. WO2015-080009 A (Patent Document 2) proposes a magnetic sputtering target that includes a high concentration phase of B and a low concentration phase of B, and in which the high concentration phase of B is finely dispersed.

[0005] In JP 2017-057477 A (Patent Document 3), (CoFe) 3 B, Co 3 B and Fe 3 There has been proposed a sputtering target material that reduces the formation of B. International Publication WO2016-140113 (Patent Document 4) discloses a magnetic material sputtering target having an oxygen content of 100 wtppm or less.

[0006] Japanese Patent Laid-Open No. 2017-82330 (Patent Document 5) and Japanese Patent Laid-Open No. 2014-156639 (Patent Document 6) disclose magnetic sputtering target materials to which rare earth (lanthanoid) elements are added. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2004-346423 A [Patent Document 2] International Publication No. 2015 / 080009 [Patent Document 3] JP 2017-057477 A [Patent Document 4] International Publication No. 2016 / 140113 [Patent Document 5] JP 2017-82330 A [Patent Document 6] JP 2014-156639 A Summary of the Invention [Problem to be solved by the invention]

[0008] In recent years, sputtering target materials made of Co-Fe-B alloys with added rare earth elements are sometimes used to improve the properties of tunnel magnetoresistive films. However, when rare earth elements are added to Co-Fe-B alloys, the Co and / or Fe that form the CoFe phase that provides toughness of the alloy and the rare earth elements form intermetallic compounds, making the sputtering target material very brittle, which can cause cracks during production or use, hindering productivity.

[0009] An object of the present invention is to provide a sputtering target material which is made of an alloy containing a rare earth element and has excellent crack resistance, and a method for producing the same. [Means for solving the problem]

[0010] As a result of extensive research, the present inventors have noticed that the addition of a specific element M to an alloy containing a rare earth element suppresses the formation of an intermetallic compound between Co or Fe and a rare earth element, which forms a CoFe phase, and thereby forms a metal structure containing a CoFe phase, and have completed the present invention.

[0011] That is, the material of the sputtering target material according to the present invention is an alloy containing B, a rare earth element RE, and an element M, with the balance being Co and / or Fe and unavoidable impurities. The content x of B in this alloy is 15 at.% or more and 30 at.% or less. The rare earth element RE is one or more selected from the group consisting of Pr, Nd, Sm, Gd, Tb, Dy, and Ho, and the total content y of the selected rare earth element RE is 0.1 at.% or more and 11 at.% or less. The element M is one or more selected from the group consisting of Cu, Ge, Sn, and Ru, and the total content z of the selected element M is 0.25 at.% or more and 13.0 at.% or less. The ratio z / y of the total content z of the element M to the total content y of the rare earth element RE is 0.5 or more and 2.5 or less.

[0012] Preferably, the alloy has a metal structure including a CoFe phase and an RE-M intermetallic compound phase including the rare earth element RE and the element M. The total content of the rare earth element RE and the element M in the RE-M intermetallic compound phase is 40 at.% or more.

[0013] From another viewpoint, the sputtering target material according to the present invention is a sintered body of a raw material powder. The material of this raw material powder is an alloy containing B, a rare earth element RE, and an element M, with the balance being Co and / or Fe and unavoidable impurities. The content x of B in this alloy is 15 at.% or more and 30 at.% or less. The rare earth element RE is one or more selected from the group consisting of Pr, Nd, Sm, Gd, Tb, Dy, and Ho, and the total content y of the selected rare earth element RE is 0.1 at.% or more and 11 at.% or less. The element M is one or more selected from the group consisting of Cu, Ge, Sn, and Ru, and the total content z of the selected element M is 0.25 at.% or more and 13.0 at.% or less. The ratio z / y of the total content z of the element M to the total content y of the rare earth element RE is 0.5 to 2.5. Effect of the Invention

[0014] The sputtering target material according to the present invention has excellent crack resistance, even though it is made of an alloy containing rare earth elements. This target material is prevented from being damaged during its manufacture and sputtering. This target material has high production efficiency. Moreover, the tunnel magnetoresistive film obtained by sputtering using this target material has excellent magnetic properties.

[0015] From another viewpoint, the manufacturing method according to the present invention makes it possible to obtain a tunnel magnetoresistive film having improved magnetic performance, and moreover to efficiently and easily manufacture a target material having excellent crack resistance. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a microscope image showing the metal structure of a sputtering target material according to one embodiment of the present invention. [Diagram 2] FIG. 2 is an example of an X-ray diffraction pattern of a sputtering target material according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, the present invention will be described in detail based on preferred embodiments. In the present specification, the term "X to Y" indicating a range means "X or more and Y or less."

[0018] The sputtering target material according to the present invention is an alloy containing B, a rare earth element RE, and an element M, with the balance being Co and / or Fe and unavoidable impurities. In other words, this alloy is a Co-Fe-B based alloy, a Co-B based alloy, or an Fe-B based alloy containing a rare earth element RE and an element M.

[0019] In the present invention, the rare earth element RE is one or more selected from the group consisting of Pr, Nd, Sm, Gd, Tb, Dy and Ho. These rare earth elements RE can contribute to improving the performance of the obtained tunnel magnetoresistive film. The element M is one or more selected from the group consisting of Cu, Ge, Sn and Ru. The element M reacts with the rare earth element RE. The reaction between the element M and the rare earth element RE suppresses the generation of intermetallic compounds between Co and / or Fe and the rare earth element that form the CoFe phase. In an alloy containing the element M together with the rare earth element RE, the formation of the CoFe phase that is responsible for toughness is not inhibited. The sputtering target material obtained using this alloy as a material has excellent crack resistance. As long as the effect of the present invention is not inhibited, this alloy may contain other elements as optional components. Examples of unavoidable impurities include O, S, C, N, etc.

[0020] The content x of B in this alloy is 15 at.% or more and 30 at.% or less. By making the content of B 15 at.% or more, the obtained tunnel magnetoresistive film is given sufficient amorphousness. This tunnel magnetoresistive film can exhibit high magnetic performance. If the content of B is 30 at.% or less, a CoFe phase can exist in the metal structure of the alloy containing the rare earth element RE and the element M.

[0021] The content y of the rare earth element RE in this alloy is 0.1 at.% or more and 11 at.% or less. When this alloy contains two or more selected from the group consisting of Pr, Nd, Sm, Gd, Tb, Dy and Ho, the total content is 0.1 at.% or more and 11 at.% or less. By making the total content of the rare earth element RE 0.1 at.% or more, the performance improvement effect of the obtained tunnel magnetoresistive film is fully exhibited. By making the total content of the rare earth element RE 11 at.% or less, the formation of the CoFe phase in the metal structure is not inhibited.

[0022] The content z of element M in this alloy is 0.25 at.% or more and 13.0 at.% or less. When this alloy contains two or more selected from the group consisting of Cu, Ge, Sn, and Ru, the total content is 0.25 at.% or more and 13.0 at.% or less. By making the total content of element M 0.25 at.% or more, the effect of suppressing the generation of intermetallic compounds between Co and / or Fe constituting the CoFe phase and the rare earth element RE is obtained. By making the total content of element M 13 at.% or less, the deterioration of film properties due to the reaction between Co and / or Fe constituting the CoFe phase and element M is avoided.

[0023] Furthermore, the ratio z / y of the total content z of element M to the total content y of rare earth element RE in this alloy is 0.5 or more and 2.5 or less. By making this ratio z / y 0.5 or more, the generation of intermetallic compounds with the rare earth element RE is suppressed, and a CoFe phase is formed. By making this ratio z / y 2.5 or less, the deterioration of film properties due to the reaction between Co and / or Fe forming the CoFe phase and element M is avoided, and the effect of improving magnetic properties by the rare earth element RE can be obtained.

[0024] The sputtering target material according to the present invention has an appropriate content of the rare earth element RE and the element M in the alloy that is the material of the target material. The formation of the CoFe phase is not inhibited in the metal structure of the alloy. The CoFe phase in the metal structure contributes to the toughness of the target material. The target material has excellent crack resistance, even though the material is an alloy containing a rare earth element. The target material is prevented from being damaged during its manufacture and sputtering. The production efficiency of the target material is high. Furthermore, by sputtering a target material made of an alloy containing the rare earth element RE, it is possible to manufacture a tunnel magnetoresistive film with excellent magnetic properties.

[0025] Preferably, the alloy constituting the sputtering target material has the following composition formula: (1-xyz)(Co-nFe)-xB-yRE-zM

[0026] In the above composition formula, n is the ratio (at.%) of Fe to the total of Co and Fe in this alloy. As long as the effects of the present invention can be obtained, n can be appropriately selected within the range of 0 at.% or more and 100 at.% or less. The (1-n) before Co is omitted.

[0027] In the above composition formula, RE is a general term for rare earth elements selected from the group consisting of Pr, Nd, Sm, Gd, Tb, Dy, and Ho, and M is a general term for elements selected from the group consisting of Cu, Ge, Sn, and Ru.

[0028] x is the ratio (at.%) of B to the sum of Co, Fe, B, RE (i.e., a rare earth element selected from the group consisting of Pr, Nd, Sm, Gd, Tb, Dy, and Ho), and M (i.e., an element selected from the group consisting of Cu, Ge, Sn, and Ru), y is the ratio (at.%) of RE to this sum, and z is the ratio (at.%) of M to this sum.

[0029] In the target material according to the present invention, x is 15 at.% or more and 30 at.% or less. From the viewpoint of magnetic properties, x is preferably 18 at.% or more.

[0030] In the target material according to the present invention, y is 0.1 at.% or more and 11 at.% or less. From the viewpoint of magnetic properties, y is preferably 3 at.% or more. From the viewpoint of crack resistance, y is preferably 10 at.% or less.

[0031] In the target material according to the present invention, z is 0.25 at.% or more and 13 at.% or less. From the viewpoint of crack resistance, z is preferably 3 at.% or more and 12.5% ​​or less.

[0032] In the target material according to the present invention, the ratio z / y is 0.5 or more and 2.5 or less. From the viewpoint of crack resistance, the ratio z / y is preferably 0.6 or more. From the viewpoint of the balance between magnetic properties and crack resistance, the ratio z / y is preferably 2.0 or less.

[0033] In the alloy containing the rare earth element RE and element M represented by the above composition formula, a metal structure containing a CoFe phase and an RE-M intermetallic compound phase containing the rare earth element RE and element M is formed. When this alloy has a metal structure containing a CoFe phase, the crack resistance of a sputtering target material made of this alloy is significantly improved. Here, in this specification, the CoFe phase means a phase formed from Fe and / or Co, and is a concept including a phase in which Co or Fe is 0 at.%, that is, an Fe phase or a Co phase. In addition, when this phase contains Co and Fe, it is referred to as a CoFe phase regardless of the ratio. The formation of the CoFe phase in the metal structure can be confirmed, for example, by the presence of peaks of αFe phase, γCo phase, and εCo phase in a diffraction pattern obtained by X-ray diffraction measurement.

[0034] Preferably, the total content of the rare earth element RE and the element M in the RE-M intermetallic compound phase formed by the reaction of the rare earth element RE and the element M is 40 at.% or more. By forming the RE-M intermetallic compound phase containing the rare earth element RE and the element M at 40 at.% or more, the formation of the CoFe phase responsible for toughness is not inhibited, and high crack resistance of the target material is obtained. From the viewpoint of improving the crack resistance, the total content of the rare earth element RE and the element M in the RE-M intermetallic compound phase is more preferably 45 at.% or more. As long as the effect of the present invention is obtained, the ratio of the rare earth element RE and the element M in the RE-M intermetallic compound phase is not particularly limited. The formation of the RE-M intermetallic compound phase in the metal structure can be confirmed, for example, by observing the cross section of a test piece taken from the target material with a scanning electron microscope (SEM). In addition, the content of the rare earth element RE and the element M in the RE-M intermetallic compound phase can be measured by energy dispersive X-ray analysis (EDX).

[0035] As long as the effects of the present invention can be obtained, the metal structure of this alloy may have other phases in addition to the CoFe phase and the above-mentioned RE-M intermetallic compound phase. 2 Examples include B phase, (CoFe)B phase, CoFeBRE phase, and CoFeRE phase.

[0036] The method for producing a sputtering target material according to the present invention includes a sintering step of sintering a raw material powder. In detail, this production method includes a step of forming a sintered body by so-called powder metallurgy, in which the raw material powder is heated under high pressure and solidified. The target material is obtained by processing this sintered body into an appropriate shape by mechanical means or the like. In other words, the sputtering target material according to the present invention is a sintered body of the raw material powder.

[0037] The raw powder is composed of a large number of particles. The material of each particle constituting the raw powder is an alloy containing B, a rare earth element RE, and an element M, with the remainder being composed of Co and / or Fe and unavoidable impurities. The content x of B in this alloy is 15 at.% or more and 30 at.% or less. The rare earth element RE is one or more selected from the group consisting of Pr, Nd, Sm, Gd, Tb, Dy and Ho. The element M is one or more selected from the group consisting of Cu, Ge, Sn and Ru. The total content y of the selected rare earth elements RE in this alloy is 0.1 at.% or more and 11 at.% or less. The total content z of the selected elements M in this alloy is 0.25 at.% or more and 13.0 at.% or less. The ratio z / y of the total content z of the elements M to the total content y of the rare earth elements RE is 0.5 or more and 2.5 or less.

[0038] In this manufacturing method, a raw material powder made of an alloy containing an appropriate amount of element M together with rare earth element RE is used, and a CoFe phase that contributes to toughness is formed in the metal structure of the target material, which is a sintered body of this raw material powder. The target material obtained by this manufacturing method has excellent crack resistance. This manufacturing method can prevent damage to the target material during its manufacture.

[0039] This raw material powder can be produced by an atomization method. The type of atomization method is not particularly limited, and may be a gas atomization method, a water atomization method, or a centrifugal atomization method. When carrying out the atomization method, a known atomization device and production conditions are appropriately selected and used.

[0040] Preferably, the raw material powder is sieved before the sintering step. The purpose of this sieving is to remove particles (coarse powder) with a particle diameter of 500 μm or more that inhibit sintering. With this raw material powder, the effects of the present invention can be obtained even if no particle size adjustment is performed other than removing the coarse powder.

[0041] The method and conditions for obtaining a sintered body by solidifying the raw material powder are not particularly limited. For example, hot isostatic pressing (HIP), hot pressing, spark plasma sintering (SPS), hot extrusion, etc. are appropriately selected. The method for processing the obtained sintered body is also not particularly limited, and known mechanical processing means can be used.

[0042] The target material, which is a sintered body of the raw material powder, is preferably used for sputtering to form a magnetic thin film used in an MTJ element, for example. This target material suppresses cracking of the target material during sputtering, even though it contains rare earth elements. This makes it possible to efficiently obtain high-performance, high-quality magnetic films suitable for magnetic devices such as magnetic heads and MRAMs. EXAMPLES

[0043] The effects of the present invention will be clarified by the following examples, but the present invention should not be construed as being limited based on the description of these examples.

[0044] Each raw material was weighed so as to obtain the composition shown in Table 1-2, and melted by induction heating in a refractory crucible in an Ar gas atmosphere or vacuum atmosphere under reduced pressure. The molten metal was then poured out from a small hole (diameter 8 mm) provided at the bottom of the crucible, and gas atomized to obtain raw material powder for manufacturing sputtering target materials of the examples and comparative examples.

[0045] The obtained raw powder was sieved to remove coarse powder with a diameter of 500 μm or more. The raw powder after sieving was filled into a can (outer diameter 220 mm, inner diameter 210 mm, length 200 mm) made of carbon steel and degassed in vacuum, and then sintered using a HIP device under conditions of temperature 900 to 1200 ° C, pressure 100 to 150 MPa, and holding time 1 to 5 hours to produce a sintered body. The obtained sintered body was processed into a disk shape with a diameter of 180 mm and a thickness of 7 mm by wire cutting, lathe processing, and surface grinding to produce a sputtering target material of the examples and comparative examples.

[0046] [Electron microscope observation] Test pieces for scanning electron microscope (SEM) were taken from each of Example No. 1-13 and Comparative Example No. 1-5. After polishing the cross section of each test piece, the cross section was observed with a scanning electron microscope (SEM) in a field of view of 45 μm vertically and 65 μm horizontally. The obtained SEM image was analyzed to measure the area of ​​the RE-M intermetallic compound phase and determine the ratio to the total field area. The average value obtained by measuring five fields is shown in Table 1-2 below as the RE-M phase area ratio (%). In addition, energy dispersive X-ray analysis (EDX) was performed on the observed RE-M intermetallic compound phase to quantify the rare earth element RE and element M, and to determine their total content. The obtained results are shown in Table 1-2 below as the RE+M content (at.%).

[0047] The SEM image obtained for Example 1 is shown in Figure 1. In Figure 1, the RE-M intermetallic phase containing the rare earth element RE and the element M is shown as reference number 1. The CoFe phase is shown as reference number 2.

[0048] [X-ray diffraction measurement] From each of the examples No. 1-13 and the comparative examples No. 1-5, test pieces were taken and subjected to XRD measurement to determine the presence or absence of the CoFe phase. Specifically, the presence of the CoFe phase was confirmed by the peaks of the αFe phase, γCo phase, εCo phase, or αCoFe phase. The obtained results are shown in Table 1-2. In Table 1-2, the presence is indicated by Y, and the absence is indicated by N.

[0049] The diffraction pattern obtained for Example 1 is shown in Figure 2. In Figure 2, the diffraction peaks indicating the presence of the αCoFe phase are indicated as ▼.

[0050] [Transverse bending strength measurement] The flexural strength was measured as an index of crack resistance for Example No. 1-13 and Comparative Example No. 1-5. Test pieces were cut out by wire cutting from each target material of the Examples and Comparative Examples, and the flexural strength was measured by a method conforming to the provisions of "JIS Z 2511". The measurement conditions were as follows. Test piece shape: thickness 2mm, width 2mm, length 20mm Distance between fulcrums: 10mm

[0051] The load (kN) when the test piece broke was measured, and the flexural strength BS (MPa) was calculated using the following formula. The average of five measured values ​​is shown in Table 1-2 below. The higher the value, the better the crack resistance. BS = (3 / 2) × P × L / (t 2 × W) t: thickness of test piece (mm) W: Width of test piece (mm) L: Distance between fulcrums (mm) P: Load at break (kN)

[0052] [Table 1]

[0053] [Table 2]

[0054] As shown in Table 1-2, the target materials of the examples have a larger flexural strength than the target materials of the comparative examples, and it is understood that the toughness due to the CoFe phase is maintained. From these evaluation results, the superiority of the present invention is clear. [Industrial Applicability]

[0055] The sputtering target material described above can be applied to the manufacture of various magnetic components. [Explanation of symbols]

[0056] 1...RE-M intermetallic compound phase (RE-M phase) 2...CoFe phase

Claims

1. The material is an alloy containing B, a rare earth element RE, and an element M, with the balance being Co and / or Fe and unavoidable impurities, The content x of B in the alloy is 15 at. % or more and 30 at. % or less, The rare earth element RE is one or more selected from the group consisting of Pr, Nd, Sm, Gd, Tb, Dy and Ho, and the total content y of the selected rare earth element RE is 3 at. % or more and 11 at. % or less; The element M is one or more selected from the group consisting of Cu, Ge, Sn, and Ru, and the total content z of the selected element M is 0.25 at. % or more and 13.0 at. % or less; A sputtering target material, wherein a ratio z / y of a total content z of the element M to a total content y of the rare earth element RE is 0.5 or more and 2.5 or less.

2. a metal structure including an RE-M intermetallic compound phase including the rare earth element RE and the element M, and a CoFe phase is formed in the alloy; 2. The sputtering target material according to claim 1, wherein the total content of the rare earth element RE and the element M in the RE-M intermetallic compound phase is 40 at. % or more.

3. A sintered body of a raw material powder, The material of the raw material powder is an alloy containing B, a rare earth element RE, and an element M, with the balance being Co and / or Fe and unavoidable impurities, The content x of B in the alloy is 15 at. % or more and 30 at. % or less, The rare earth element RE is one or more selected from the group consisting of Pr, Nd, Sm, Gd, Tb, Dy and Ho, and the total content y of the selected rare earth element RE is 3 at. % or more and 11 at. % or less; The element M is one or more selected from the group consisting of Cu, Ge, Sn, and Ru, and the total content z of the selected element M is 0.25 at. % or more and 13.0 at. % or less; A sputtering target material, wherein a ratio z / y of a total content z of the element M to a total content y of the rare earth element RE is 0.5 or more and 2.5 or less.

Citation Information

Patent Citations

  • Soft magnetic film, planar-type magnetic element using soft magnetic film, filter and thin-film magnetic head

    JP2001217125A

  • Fe-Co-B ALLOY TARGET MATERIAL, ITS MANUFACTURING METHOD, SOFT MAGNETIC FILM, MAGNETIC RECORDING MEDIUM AND TMR ELEMENT

    JP2004346423A

  • CoFe-BASED ALLOY FOR SOFT MAGNETIC FILM LAYERS IN PERPENDICULAR MAGNETIC RECORDING MEDIA, AND SPUTTERING TARGET MATERIAL

    JP2014156639A

  • CoFeB BASED ALLOY TARGET MATERIAL

    JP2017057477A

  • CoFe-BASED ALLOY FOR SOFT MAGNETIC FILM LAYER IN PERPENDICULAR MAGNETIC RECORDING MEDIUM AND SPUTTERING TARGET MATERIAL

    JP2017082330A